Influência de Harpagophytum procumbens sobre parâmetros comportamentais e moleculares em um modelo de discinesia orofacial em ratos - Schaffer, Larissa Finger (2017)
Fluphenazine is a typical antipsychotic used for the treatment of schizophrenia. However, its chronic use has been related to the appearance of extrapyramidal side effects, such as tardive dyskinesia (TD). Studies suggest the involvement of neuroinflammation as well as oxidative stress (OS), as possible causes for the onset of DT, which can also lead to dopaminergic neurodegeneration. Harpagophytum procumbens (HP) is a herbal medicine used in the clinic mainly due to its anti-inflammatory effects. Thus, the objective of this study was to evaluate the influence of HP on behavioral, biochemical and molecular parameters in fluphenazine-induced orofacial dyskinesia (OD) model in rats. First, we analyzed several fractions of HP by high performance liquid chromatography and performed the radical-scavenging activity DPPH assay. In order to choose a fraction that presented greater amount of harpagoside and that had a good antioxidant activity in vitro, where we chose the ethyl acetate fraction of H. procumbens (EAF HP). Thus, we verified the effect of EAF HP (10, 30 and 100 mg / kg-21 days) on fluphenazine-induced OD (25 mg / kg single dose) in rats through motor behavioral parameters. In addition, we performed biochemical serological analyzes, OS parameters (in liver, kidney, cortex and striatum), proinflammatory cytokines (in striatum and cortex), immunoreactivity of tyrosine hydroxylase (TH), dopamine transporter (DAT), dopamine receptor subtype D2 (DRD2), glutamate decarboxylase (GAD) and cyclooxygenase 2 (COX 2) (in striatum). Chronic administration of fluphenazine significantly increased vacuos chewing movements (VCMs) at all analyzed times (2, 7, 14 and 21 days) and this increase was inhibited by EAF HP, especially at the dose of 30 mg / kg, on days 7, 14 and 21. Fluphenazine decreased locomotion and exploratory activity, however EAF HP did not protect against this change. Fluphenazine induced OS identified by changes in catalase activity and levels of reactive oxygen / nitrogen species (RS) in the cortex and striatum. In addition, it increased all proinflammatory cytokines, and showed a tendency to increase COX 2 levels. However, it did not modify the immunoreactivity of TH, DAT, DRD2 and GAD. The effects of fluphenazine were reduced by administration of HP EAF especially in the striatum, which structure is related to motor control. Moreover, this fraction proved to be safe, because none of the doses tested showed a change in the biochemical parameters in serum and OS in the liver and kidneys of animals. Our results suggest the involvement of OS and neuroinflammation fluphenazine-induced in the development of OD in rats and points to EAF HP as a promising therapeutic agent for the treatment of oral involuntary movements.